2017
DOI: 10.1021/jacs.6b10734
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Reducing Vapor Atmosphere in the Fabrication of Tin-Based Perovskite Solar Cells

Abstract: Tin-based halide perovskite materials have been successfully employed in lead-free perovskite solar cells, but the tendency of these materials to form leakage pathways from p-type defect states, mainly Sn and Sn vacancies, causes poor device reproducibility and limits the overall power conversion efficiencies (PCEs). Here, we present an effective process that involves a reducing vapor atmosphere during the preparation of Sn-based halide perovskite solar cells to solve this problem, using MASnI, CsSnI, and CsSn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
525
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 528 publications
(537 citation statements)
references
References 44 publications
9
525
2
1
Order By: Relevance
“…Moreover, a hydrazine atmosphere can help the disperse of SnI 2 65 to improve the quality of perovskite film, as indicated by no observable agglomeration of SnI 2 from the SEM/EDS characterization (Figure 10d–i). The corresponding device displayed the best PCE (4.81%) of CsSnI 3 ‐based PSCs, which is in the meantime much higher than the SnF 2 41 modified devices (1.83%). Additionally, triethyl phosphine (TEP)63 as a soft Lewis base can form intermediate complexes with Sn 2+ species via weak coordinating interaction, which could slow down the perovskite crystallization process and improve the film morphology as well as the device performance.…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 86%
See 4 more Smart Citations
“…Moreover, a hydrazine atmosphere can help the disperse of SnI 2 65 to improve the quality of perovskite film, as indicated by no observable agglomeration of SnI 2 from the SEM/EDS characterization (Figure 10d–i). The corresponding device displayed the best PCE (4.81%) of CsSnI 3 ‐based PSCs, which is in the meantime much higher than the SnF 2 41 modified devices (1.83%). Additionally, triethyl phosphine (TEP)63 as a soft Lewis base can form intermediate complexes with Sn 2+ species via weak coordinating interaction, which could slow down the perovskite crystallization process and improve the film morphology as well as the device performance.…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 86%
“…As an example, hypophosphorous acid (HPA)73 ( Figure 9 a) was introduced into fabricating all‐inorganic CsSnIBr 2 ‐based mesoscopic PSCs to reduce the concentration of Sn vacancies, achieving a higher PCE of 3.0% than 1.7% of without HPA addition. Moreover, Song et al41 introduced hydrazine vapor (reducing vapor atmosphere) in the presence of SnF 2 additive into fabrication process of Sn‐based PSCs (Figure 9b). The results showed that the additional hydrazine vapor process led to significantly suppressed carrier recombination with more than 20% reduction of Sn 4+ /Sn 2+ ratios.…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%
See 3 more Smart Citations